Exoenzyme T Plays a Pivotal Role in the IFN-γ Production after Pseudomonas Challenge in IL-12 Primed Natural Killer Cells - Vourc’h, Mickael; Roquilly, Antoine; Broquet, Alexis; David, Gaelle; Hulin, Philippe; Jacqueline, Cedric; Caillon, Jocelyne; Retiere, Christelle; Asehnoune, Karim (Frontiers in Immunology, 2017)
Pseudomonas aeruginosa (PA) expresses the type III secretion system (T3SS) and effector exoenzymes that interfere with intracellular pathways. Natural killer (NK) cells play a key role in anti-bacterial immunity and their activation is highly dependent on IL-12 produced by myeloid cells. We studied PA and NK cell interactions and the role of IL-12 using, human peripheral blood mononuclear cells, sorted human NK cells and a human NK cell line (NK92). We used a wild-type (WT) strain of PA (PAO1) or isogenic PA deleted strains to delineate the role of T3SS and exoenzymes. Our hypotheses were tested in vivo in a PA-pneumonia mouse model. Human NK cells or NK92 cell line produced low levels of IFN-g in response to PA without IL-12 stimulation, whereas PA significantly increased IFN-g after IL-12 priming. The modulation of IFN-g production by PA required bacteria-to-cell contact. Among Type III secretion system (T3SS) effectors, exoenzyme T (ExoT) up-regulates IFN-g production and control ERK activation. In vivo, ExoT also increases IFN-g levels and the percentage of IFN-g+ NK cells in lungs during PA pneumonia, confirming in vitro data. In conclusion, our results suggest that T3SS could modulate the production of IFN-g by NK cells after PA infection through ERK activation.